3(x+11)=11x-19

Simple and best practice solution for 3(x+11)=11x-19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+11)=11x-19 equation:


Simplifying
3(x + 11) = 11x + -19

Reorder the terms:
3(11 + x) = 11x + -19
(11 * 3 + x * 3) = 11x + -19
(33 + 3x) = 11x + -19

Reorder the terms:
33 + 3x = -19 + 11x

Solving
33 + 3x = -19 + 11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11x' to each side of the equation.
33 + 3x + -11x = -19 + 11x + -11x

Combine like terms: 3x + -11x = -8x
33 + -8x = -19 + 11x + -11x

Combine like terms: 11x + -11x = 0
33 + -8x = -19 + 0
33 + -8x = -19

Add '-33' to each side of the equation.
33 + -33 + -8x = -19 + -33

Combine like terms: 33 + -33 = 0
0 + -8x = -19 + -33
-8x = -19 + -33

Combine like terms: -19 + -33 = -52
-8x = -52

Divide each side by '-8'.
x = 6.5

Simplifying
x = 6.5

See similar equations:

| x^8-7x^7-3x^6= | | (4x+1)(2x^2+x+1)= | | 7x^3+6x^2-2= | | 2cx-1=0 | | 2c*-1=0 | | 5x+18=4x | | i=101x-201526 | | 5x-2=-27 | | 4x^2+8x+32=0 | | 32-11= | | (v+7w)x(3v+3w-1)= | | 22-42-4(x-1)-4= | | 113-7x=20x+20 | | 6x+18=328 | | 7h+4-3h+2= | | 2bc+8b-3c-12= | | x^3+8x^2+2x+16= | | 5x+12=220 | | .66a+2=1.33a+.33 | | 7a(2a-b)+3(2a-b)= | | 17z+234=2213 | | (6x^2-31x+5)(x-5)= | | 16x-18=224 | | 4a=2a+14 | | ta=ma-s | | .66a+2=1.33a+1 | | h(3)= | | (6x+7)(3x+2)= | | 21x-35=20x-45 | | 0.5n=9 | | 12=50-30x | | e^2x=42 |

Equations solver categories